Cultural formation of preferences and assimilation of cultural groups - Michael M. Pichler (Bielefeld University, Institute of Mathematical Economics (IMW), 2010)
Based on the cultural formation of continuous preferences framework of Pichler [16], this paper analyzes the evolution of preferences and behavior in a two cultural groups setting. We show that the qualitative dynamic properties depend crucially on what parents perceive as the optimal preferences for their children to adopt. Under inter- generationally fixed optimal preferences, the preferences of the cultural groups will always stay distinct. If the optimal preferences coincide with those derived from the representative group behavior, then a multitude of convergence path types can realize. These contain both an inter-generational assimilation process toward the same preference point, as well as inter-generational dissimilation.
urn:nbn:de:hbz:361-14290
Keywords: C72; J13; Z13; 330; Continuous Preferences; Assimilation; Cultural Groups; Endogenous Preferences; Preference Evolution; Socialization; Kulturpsychologie; Sozialisation; Soziale Integration; Soziale Werte; Overlapping Generations; Theorie